Internet of things A to Z : technologies and applications - Hassan, Qusay F., 1982- (Hoboken, New Jersey : John Wiley and Sons, Inc., 2018)
A comprehensive overview of the Internet of Things' core concepts, technologies, and applications Internet of Things A to Z offers a holistic approach to the Internet of Things (IoT) model. The Internet of Things refers to uniquely identifiable objects and their virtual representations in an Internet-like structure. Recently, there has been a rapid growth in research on IoT communications and networks, that confirms the scalability and broad reach of the core concepts. With contributions from a panel of international experts, the text offers insight into the ideas, technologies, and applications of this subject.
Part II: EnablersChapter 3: An Overview of Enabling Technologies for the Internet of Things; 3.1 Introduction; 3.2 Overview of IoT Architecture; 3.3 Enabling Technologies; 3.3.1 Perception Layer Technologies; 3.3.1.1 Passive; 3.3.1.2 Semipassive; 3.3.1.3 Active; 3.3.2 Network Layer Technologies; 3.3.2.1 Identification; 3.3.2.2 Communication; 3.3.2.3 Security; 3.3.2.4 Routing; 3.3.3 Middleware Technologies; 3.3.3.1 Service Discovery; 3.3.3.2 Data Exchange; 3.3.3.3 Computation; 3.3.4 Application Layer Technologies; 3.3.4.1 Identity-Related Services; 3.3.4.2 Information Aggregation Services
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed May 16, 2018).
Keywords: Internet of things; COMPUTERS / Computer Literacy; COMPUTERS / Computer Science; COMPUTERS / Data Processing; COMPUTERS / Hardware / General; COMPUTERS / Information Technology; COMPUTERS / Machine Theory; COMPUTERS / Reference; Internet of things; Electronic books